Design details recognized as the reasons of defects of reinforced concrete floors in the multi-storey garage - Szerafin, Jerzy; Halicka, Anna (Budownictwo i Architektura / Civil and Architectural Engineering, 2016)
In the paper a ‚case study’ of a six-storey garage is described. Soon after the beginning of use the cracking and other damages of reinforced concrete floor slabs as well as stagnant pools of water on them were observed. The poor concrete, improper design solution regarding the slabs inclinations and distribution of pipes removing the rain water were recognized as causes of these damages.